ANALISIS PENGARUH PROMOSI IKLAN DAN PEMASARAN LANGSUNG TERHADAP PENDAPATAN PADA HOTEL TOPAS GALERIA BANDUNG - Arni Kurniati (Jurnal Manajemen FE-UB, 2014)
Until now Hotel Topas Galeria Bandung included in hotel class have star of 3 wishful boost up the class of midst emulation of the hotel business progressively tighten in globalization era. Dwelling room; chamber storey level is in actual in this time newly reach 70% where Hotel Topas Galeria have the goals equal to 73%. When Hotel Topas Galeria can boost up the Hotel class storey; level and room chamber dwelling storey; level hence expected also can improve earnings. Though Hotel Topas Galeria have done the efforts in permeating the consumer by paying attention the service quality and done activity of promotion hotchpotch but this matter still not yet meanly to grafity the hotel management to storey; level earnings of hotel till now as posed at by room; chamber dwelling storey; level which have been reached (70%). With above reason writer interest to do the research  concerning relation between promotion hotchpotchs (direct marketing and advertisement promotion) with earnings Hotel Topas Galeria. Analysis framework the used in influence and strategy marketing of hotel. Analysis method the used is analysing descriptive and inferensial, with correlation statistical methods and regresi doubled linear which continued with hypothesis test (test t) at real level 1%. Where data collected by using technique  purposive sample for the data of correlation and regresi doubled linear where direct marketing and advertisement promotion used data 68 months from January 1998 until August 2003. Analysis result indicate that the direct marketing and advertisement promotion have the influence each of 91,5% and 86,7% to earnings storey; level Hotel Topas Galeria and significant real level 1%. And so do there are influence of direct marketing and advertisement promotion togetherly to total earnings is, equal to 84,1% is while the rest of 15,9% is influence of other factors be like sales promotion, publication or personal selling and others. Equation regresi doubled linear is Y = -24047,1 + 58,013 X1 – 15,633 X2. After test the hypothesis use the real level 1% known that advertisement promotion really influential significantly to earnings of hotel is while direct marketing of his influence don’t significant to earnings of hotel. For marketing Hotel Topas Galeria more intensively again advertisement promotion and direct marketing better transferred to other marketing technique be like sales promotion with gift of discount, exhibition trade and others.